Korelasi Air Entry Value (AEV) Dengan Kuat Geser Tanah Jenuh Sebagian - Gayuh Aji Prasetyaningtiyas; Kuswaji Dwi Priyono (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2022)
The characteristics of unsaturated soil seen from the Groundwater Characteristics Curve (SWCC). One of main variables determine the SWCC of soil are Air Entry Value (AEV). The AEV is the initial point of air entering the soil void. SWCC was obtained from the fitting of unsaturated soil model from Soil Vision. Although statistically a fitting model can match the point of laboratory result, the AEV resulted different point from the curve shaped by laboratory points. Therefore, this study aims to understand further the influence of AEV on unsaturated particularly on the change of soil share strength parameters. This studi used field investigation, a series of laboratory and numerical analysis to obtain Fredlund bimodal and Van Genutchen fitting model. Both models, then used to calculate the shear strength parameter (φ’, c’) change affected by different water content. On the other hand, the AEV consider as the major aspect on the calculation. The result shows that Van Genutchen model demonstrated the higher similarity with the laboratory test shear strength test comparing to Fredlund Bmodal’s. for silt sand oil in this study. This study is applicable for back filled and landslide case.